SAT0470 Secukinumab provides sustained improvements in the signs and symptoms of active psoriatic arthritis: 3-year efficacy and safety results from phase 3 future 1 trial. (15th June 2017) - Mease, PJ; Kavanaugh, A; Reimold, A; Tahir, H; Rech, J; Hall, S; Geusens, P; Pascale, P; Delicha, EM; Pricop, L; Mpofu, S; ,
Abstract : Background: Secukinumab significantly improved the signs and symptoms of psoriatic arthritis (PsA) over 2 years (yrs) in the FUTURE 1 study. 1 Objectives: To report efficacy and safety of secukinumab through 3 yrs in an extension of the FUTURE 1 study (NCT01892436 ). Methods: After 2-yr core trial, patients (pts) receiving secukinumab 150/75mg s.c. entered the 3-yr extension phase. Efficacy results at Week (Wk) 156 are presented for those pts originally randomised to secukinumab (n=308) and included ACR20/50/70, PASI 75, DAS28-CRP, SF-36 PCS, HAQ-DI, dactylitis and enthesitis. Multiple imputation was used for analysis of binary variables while continuous variables are reported as observed. Analyses by anti-TNF status (naïve/inadequate response) were prespecified and reported as observed. Safety analysis included all pts (n=587) who received ≥1 dose of secukinumab. Results: Overall, 457 of the original 606 pts entered the extension study of which 435 (95.2%) pts completed 156 wks (151 [93.8%] pts in IV→150 mg group; 142 [96.6%] in IV→75 mg group; 142 [95.3%] in PBO→ secukinumab groups). Sustained clinical improvements through Wk 156 were observed across all endpoints and were seen regardless of prior anti-TNF use (Table 1 ). Over the entire study period (mean [±SD] exposure to secukinumab of 1025.1±372.7 days), the exposure-adjusted incidence rate with secukinumab for serious infections/infestations, candida infections, Crohn's disease, and malignant/unspecified tumors was 1.7 (27), 1.2 (17), 0.1 (2), and 0.9 (14) per 100 pt-yrs, respectively. Conclusions: Secukinumab provided sustained improvements in signs/symptoms and across multiple clinical domains of active PsA in pts who completed 3 yrs of therapy. Secukinumab was well tolerated with a favorable safety profile consistent with that previously reported. 1 References: Kavanaugh A, et al. Arthritis Care Res. (Hoboken) 2016. Disclosure of Interest: P. Mease Grant/research support from: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Consultant for: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, A. Kavanaugh Consultant for: Novartis, A. Reimold Grant/research support from: AbbVie, H. Tahir Speakers bureau: Novartis, Eli Lilly, and Abbvie, J. Rech Speakers bureau: Abbvie, BMS, Celgene, Fresenius, medicap, MSD, Novartis, Pfizer, and Roche, S. Hall: None declared, P. Geusens Grant/research support from: Pfizer, Abbott, Lilly, Amgen, MSD, Will, Bio Minerals and Roche, Speakers bureau: Pfizer, Abbott, Lilly, Amgen, MSD, Will, Bio Minerals and Roche, P. Pascale Shareholder of: Novartis, Employee of: Novartis, E. M. Delicha Employee of: Novartis, L. Pricop Shareholder of: Novartis, Employee of: Novartis, S. Mpofu Shareholder of: Novartis, Employee of: Novartis